2016
DOI: 10.1155/2016/9848041
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Lopinavir/Ritonavir Is Associated with Fewer Adverse Events in Infants than Nelfinavir or Atazanavir

Abstract: Combination antiretroviral therapy (cART) is successfully used for prevention of perinatal HIV transmission. To investigate safety, we compared adverse events (AE) among infants exposed to different maternal cART regimens. We reviewed 158 HIV-uninfected infants born between 1997 and 2009, using logistic regression to model grade ≥1 AE and grade ≥3 AE as a function of maternal cART and confounding variables (preterm, C-section, illicit drug use, race, ethnicity, infant antiretrovirals, and maternal viremia). Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…Hepatic changes at birth was a frequent adverse effect in our cohort (36%) associated mostly with NVP exposure. Consistent with our results, one recent American study showed that children exposed to lopinavir/ritonavir presented lower incidence of hematological and hepatic changes [ 40 ]. However, in other studies no association was found between hepatic change and specific drug regimens, including a Brazilian study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hepatic changes at birth was a frequent adverse effect in our cohort (36%) associated mostly with NVP exposure. Consistent with our results, one recent American study showed that children exposed to lopinavir/ritonavir presented lower incidence of hematological and hepatic changes [ 40 ]. However, in other studies no association was found between hepatic change and specific drug regimens, including a Brazilian study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Characteristics of included studies are summarised in Table 1 . 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 11 prospective (32%) and 23 retrospective (68%) cohort studies analysed data from 57,546 WLHIV in 22 countries ( Table 1 ). 24 studies (71%) took place in high income countries (HICs), and 10 studies (29%) took place in LMICs ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…40 France High Retrospective 2005 to 2015 1597 Women enrolled from French Perinatal Cohort Regression analysis, risk factor analysis LNMP confirmed by ultrasound Average Smith et al. 59 USA High Retrospective 1997 to 2009 158 Twins excluded, data from Children's Hospital Immunodeficiency Program (CHIP), 12% IDU None No description Poor Snijdewind et al. 41 Netherlands High Retrospective 1/1997 to 2/2015 1392 Twins excluded, women recruited from 26 nationwide sites, 10.8% smoking, 11.7% alcohol use, 0.6% IDU Risk factor analysis Early ultrasound or LNMP Average Szyld et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 While their common mechanism of action supports an assumption that drugs within a class would behave similarly, and some studies have documented similar rates of outcomes, 40 there are also specific individual drugs which may confer increased or decreased risk as compared to others within the same class. 1,41,42 For example, the drug efavirenz (EFV) has been more commonly associated with psychiatric adverse effects than other drugs within the NNRTI class. 42 Given a plausible biological justification, the hierarchical modeling approach thus seems appealing.…”
Section: Introductionmentioning
confidence: 99%